Agronomic biofortification of food crops: An emerging opportunity for global food and nutritional security - Bhardwaj, Ajay Kumar; Chejara, Sukirtee; Malik, Kapil; Kumar, Raj; Kumar, Ashwani; Yadav, Rajender Kumar (Frontiers in Plant Science, 2022)
Fortification of food with mineral micronutrients and micronutrient supplementation occupied the center stage during the two-year-long Corona Pandemic, highlighting the urgent need to focus on micronutrition. Focus has also been intensified on the biofortification (natural assimilation) of mineral micronutrients into food crops using various techniques like agronomic, genetic, or transgenic. Agronomic biofortification is a time-tested method and has been found useful in the fortification of several nutrients in several crops, yet the nutrient use and uptake efficiency of crops has been noted to vary due to different growing conditions like soil type, crop management, fertilizer type, etc. Agronomic biofortification can be an important tool in achieving nutritional security and its importance has recently increased because of climate change related issues, and pandemics such as COVID-19. The introduction of high specialty fertilizers like nano-fertilizers, chelated fertilizers, and water-soluble fertilizers that have high nutrient uptake efficiency and better nutrient translocation to the consumable parts of a crop plant has further improved the effectiveness of agronomic biofortification. Several new agronomic biofortification techniques like nutripriming, foliar application, soilless activation, and mechanized application techniques have further increased the relevance of agronomic biofortification. These new technological advances, along with an increased realization of mineral micronutrient nutrition have reinforced the relevance of agronomic biofortification for global food and nutritional security. The review highlights the advances made in the field of agronomic biofortification via the improved new fertilizer forms, and the emerging techniques that achieve better micronutrient use efficiency of crop plants.